The shadowy realm of news avoidance: Exploring public service news avoidance as negative social action - Lindell Johan; Basta Zofie; Brieger Alexandra; Fukada Sayaka; Greiner Sarah; Marcora Marta; Mc Taggart Christopher (Nordicom Review)
Studies on news avoidance rely on a range of theories to explain why news avoidance takes place and its potential consequences, and the debates on different ways of measuring news avoidance have been lively. Despite the numerous approaches and conceptualisations, there is room to theorise what news avoidance entails as a social phenomenon. In this study, we posit that news avoidance can fruitfully be approached as a form of negative social action embedded in a negative social space – a realm of the lifeworld filled with non-doings and non-appearance. We apply this approach, which opens up new questions in the field of news avoidance studies, to a case study of Swedes who opted out of national public service news in the midst of the Covid-19 pandemic. Findings suggest that avoiders of public service news occupy relatively precarious social positions, and that news avoidance is embedded in a broader negative social space.